Determination and control of longshore sediment transport:: A case study - Ari, H. Anil; Yuksel, Yalcin; Cevik, Esin Ozkan; Guler, Isikhan; Yalciner, Ahmet Cevdet; Bayram, Bulent (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The fishery harbor of Karaburun coastal village is located at the south west coast of the Black Sea. The significant waves coming from north eastern direction cause considerable rate of sediment transport along 4 km sandy beach towards the fishery harbor in the region. The resulting sediment deposition near and inside the harbor entrance prevents the boat traffic and cause a vital problem for the harbor operations. In order to determine the level and reasons of the sediment transport, the long-term observations of shoreline changes, the long-term statistical analysis of wind and wave characteristics in the region, and sediment properties have been performed. The data obtained from observations, measurements and analysis were discussed. The long-term statistics of deep water significant wave heights for each direction was discussed by comparing the results obtained from different data sources and methods. For shoreline evolution, the numerical study using one-line model was applied to describe the shoreline changes with respect to probable wave conditions. Initial shoreline was obtained from the digitized image in 1996 since there was no previous shoreline measurement of the site. The results were compared using the techniques of remote sensing obtained from sequent images using IKONOS and IRSIC/D satellites. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: shoreline change; coastal sediment transport; longshore sediment transport; coastal zone management; remote sensing; Engineering; Oceanography